1987
DOI: 10.1007/bf01849399
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two insertions of 100-minute releasing quinacrine hydrochloride pellets for non-surgical female sterilization

Abstract: Extensive research has been undertaken to develop a simple method of non-surgica/ female sterilization. Zipper and associates identified quinacrine hydrochloride as a drug likely to produce tubal occlusion when placed into the uterus. Zipper's early work with a solution of quinaerine led to the development of quinacrine pellets, a delivery system that was designed to bring the quinacrine into prolonged contact with the tubal ostia through extended uterine retention.Three transcervica/ uterine insertions of 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Other reports of two or three insertions have given similar results [4,[16][17][18][19][20][21]. Hieu and his co-workers [4] noted great variation in efficacy among inserting clinicians and hypothesized that this was due to different insertion techniques.…”
Section: Efficacysupporting
confidence: 51%
“…Other reports of two or three insertions have given similar results [4,[16][17][18][19][20][21]. Hieu and his co-workers [4] noted great variation in efficacy among inserting clinicians and hypothesized that this was due to different insertion techniques.…”
Section: Efficacysupporting
confidence: 51%
“…Eligible women were asked to come to the clinic in the proliferative phase of their cycle where a physical and pelvic examination was performed. Systematically, every other subject was administered transcervically, as described by Zipper [1], six pellets of quinacrine (216 mg) and three pellets of diclofenac (75 mg) or three pellets of ibuprofen (55.5 mg). The insertions were repeated a month later.…”
Section: Methodsmentioning
confidence: 99%
“…The quinacrine pellet method of nonsurgical female sterilization as developed by Zipper and his colleagues [1] involves transcervical administration of 252 mg quinacrine hydrochloride as seven pellets through a modified Copper T intrauterine device (IUD) inserter. Two doses a month apart are given to nonpregnant women during the proliferative phase of the menstrual cycle (days 5 to 12).…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1970s and early 1980s, Zipper et al [5], in Chile, with the help of Family Health International (FHI), began performing phase I clinical trials in women using, first, a 10-minute release formulation of quinacrine pellets requiring three separate insertions, and then a 100-minute release formulation requiring two insertions. The investigators reported a 12-month failure rate of 3.3 and 2.0 respectively, with follow-up of 80% of the study cases.…”
Section: Introductionmentioning
confidence: 99%